2015
DOI: 10.5614/j.eng.technol.sci.2015.47.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Flour Fractions from Five Yam (Dioscorea alata) Cultivars in Indonesia

Abstract: Abstract. The purpose of this study was to investigate the influence of particle size on the chemical properties of yam flour in five cultivars, yellow/YY, orange/OY, light purple/LPY, purple/PY, and dark purple/DPY. With a mesh sieve, three flour fractions were separated according to particle size: small (128.6-139.7 µm), medium (228.7-257.9 µm), and large (475.4-596.3 µm). The content of moisture (6.81-11.26 %db) and lipids (4.48-9.85 %db) decreased with the increase of particle size, while proteins (4.48-9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Water yam flour carbohydrate content in this study was comparable to earlier reported values [39,40]. However, Ezeocha and Ojimelukwe [33] reported a lower value for carbohydrate content of water yam.…”
Section: Raw Flour Carbohydrate Contentsupporting
confidence: 89%
“…Water yam flour carbohydrate content in this study was comparable to earlier reported values [39,40]. However, Ezeocha and Ojimelukwe [33] reported a lower value for carbohydrate content of water yam.…”
Section: Raw Flour Carbohydrate Contentsupporting
confidence: 89%
“…However, it was lower than that reported by Baah, Maziya-Dixon, Asiedu, Oduro, & Ellis (2009) that showed protein content ranged from 4.3% to 8.7%. It was also considered lower than the previous study subjected to other local accessions of water yam in Indonesia by Nadia et al (2015) showing that the protein content ranged between 4.48% to 9.85%. Nonetheless, in average the protein content of water yam local accessions in the present study was higher than that of other tuber and root crops reported by Chandrasekara & Josheph Kumar (2016) also Haytowitz et al (2019), such as cassava (1.4%), sweet potato (1.6%), and quite similar to potato (2.57%).…”
Section: Biochemical Composition and Nutritional Valuementioning
confidence: 60%
“…Genotype is a main source of variability in the micronutrient content in starchy resources as reported in sweet potato, yam, and banana (Nadia et al., ; Shih, Kuo, & Chiang, ; Singh, Pal Singh, Kaur, & Singh, ). In yam, species influence total phenolic content.…”
Section: Influence Of Intrinsic Factors Such As Genotype and Tissue Omentioning
confidence: 99%
“…However, most studies on the phenolic profile have dealt with HPLC or HP‐TLC techniques (Champagne et al., ; Lebot et al. ; Nadia et al., ). So, individual phenols have been tentatively identified.…”
Section: Influence Of Intrinsic Factors Such As Genotype and Tissue Omentioning
confidence: 99%